Fabrication of high-performance carbon nanotube/copper composite fibers by interface thiol-modification. (9th July 2022) - Guo, Lei; Li, Huifang; Liu, Dandan; Zhou, Yurong; Dong, Lizhong; Zhu, Siqi; Wu, Yulong; Yong, Zhenzhong; Kang, Lixing; Jin, Hehua; Li, Qingwen
Abstract: Carbon nanotube (CNT)/copper (Cu) composite fibers are placed great expectations as the next generation of light-weight, conductive wires. However, the electrical and mechanical performances still need to be enhanced. Herein, we demonstrate a strategy that is electrodeposition Cu on thiolated CNT fibers to solve the grand challenge which is enhancing the performance of CNT/Cu composite fibers. Thiol groups are introduced to the surface of the CNT fibers through a controllable O2 plasma carboxylation process and amide reaction. Compared with CNT/Cu composite fibers, there are 82.7% and 29.6% improvements in electrical conductivity and tensile strength of interface thiol-modification composite fibers. The enhancement mechanism is also explored that thiolated CNT fibers could make strong interactions between Cu and CNT, enhancing the electrical and mechanical performance of CNT/Cu composites. This work proposes a convenient, heat-treatment-free strategy for high-performance CNT/Cu composite fibers, which can be manufactured for large-scale production and applied to next-generation conductive wires.